STRATEGI GURU DALAM MEMOTIVASI BELAJAR SISWA KELAS IV SD NEGERI 170 PEKANBARU - Nurma Yunita; Siti Quratul Ain (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
The teacher's strategy to increase students’ motivation is needed during the learning process. The teacher’s motivation will make students always enthusiastic about achieving learning goals. The purpose of the study was to find out how the classroom teacher's strategies and classroom teachers' obstacles in motivating students' learning are seen. The research method was qualitative research with a field research model. The data were collected through observation, interviews, and documentation. The result showed that the teacher has a strategy to motivate students’ learning activities like explaining goal achievement, increasing their interest, making a good atmosphere in the teaching and learning process, applying an attractive method, giving appreciation for the success, and providing additional scores during the learning process. The obstacles came from the students who were still lazy to study, made noise in the classroom and did not listen to the teacher, the students who were afraid to express opinions, not all students who preferred the learning method applied by the teacher, and the students who were lazy to write and did not want to follow the rules due to some differences of students’ character. The Suggestions or research recommendations were intended for teachers to change students’ learning methods or strategies frequently in motivating students in terms of conditions and circumstances when studying.